On Some Maps Concerning Beta Closed Sets and Related Groups (Global Journal of Science Frontier Research, 2019)
The concept of group of functions, say βch(X,τ) preserving β-closed sets containing homeomorphism group h(X,τ) was studied by Arora,Tahiliani and Maki. In continuation to that, we study some new isomorphisms, mappings, subgroups and their properties.
Keywords: 3B1; -open; 3B2; -open and 3B2; -irresolute mappings